2012
DOI: 10.7314/apjcp.2012.13.9.4295
|View full text |Cite
|
Sign up to set email alerts
|

Human Embryonic Stem Cells - a Potential Vaccine for Ovarian Cancer

Abstract: In contrast, rats in Group 4 did not display any elevation of antitumour responses. Western blot analysis found cross-reactivity among antibodies generated between H9 and NuTu-19. However, the cytokines did not show significant differences, and no side effects were detected. Conclusion: hESC-based vaccination is a promising modality for immunotherapy of ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
3
16
0
Order By: Relevance
“…With the in-depth study of tumors, it was found that the occurrence, development and metastasis were associated with the surrounding environment of tumors (13). There is a biphasic and dynamic interaction between the tumor microenvironment and tumor cells (15). Studies have shown that the embryonic microenvironment can alter the biological behavior of malignant tumor cells, and that cytokines secreted by ESCs regulate the proliferation and invasion of some tumor cells (15,16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the in-depth study of tumors, it was found that the occurrence, development and metastasis were associated with the surrounding environment of tumors (13). There is a biphasic and dynamic interaction between the tumor microenvironment and tumor cells (15). Studies have shown that the embryonic microenvironment can alter the biological behavior of malignant tumor cells, and that cytokines secreted by ESCs regulate the proliferation and invasion of some tumor cells (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…There is a biphasic and dynamic interaction between the tumor microenvironment and tumor cells (15). Studies have shown that the embryonic microenvironment can alter the biological behavior of malignant tumor cells, and that cytokines secreted by ESCs regulate the proliferation and invasion of some tumor cells (15,16). In addition, owing to fewer ESC antigens being expressed in normal tissues compared with traditional cancer vaccines, ESCs cause fewer autoimmune responses while killing tumor cells (17).…”
Section: Discussionmentioning
confidence: 99%
“…Main concerns are the possibility of tetratoma formation and induction of autoimmunity [11,104,105]. In comparison to a xenogeneic source, allogeneic ESCs and autologous iPSCs-based vaccines were found more effective to prevent tumor relapse in mice, as evidenced by enhanced immune cell proliferation and cytotoxic cytokine production [104][105][106][107]. However, these vaccines should be used as prophylactic treatment rather than as a therapeutic treatment.…”
Section: Stem Cell-based Anti-cancer Vaccinesmentioning
confidence: 99%
“…Metastatic breast cancer cells have been linked to embryonic stem cells (ESCs) due to their sharing of certain similar gene signatures and convergence of tumorigenic and embryonic pathways (e.g., EGFR, Wnt/β-catenin, and TGF-β) [2][3][4] . ESC microenvironments have been exploited to restrict metastatic potential of cancer cells [5][6][7] . In particular, our previous studies have shown that bioengineered 3D ESC microenvironments using alginate hydrogels have great potential to supply critical signaling molecules and reprogram highly aggressive breast cancer cells to a non-invasive phenotype [4,[8][9][10] , including decreased cell proliferation, increased apoptosis, reduced cell migration, invasion and metastatic marker expression, reversed epithelial-mesenchymal transition (EMT), and altered cell metabolism of metastatic breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%